Partnership for inclusive growth: Can linkages with large firms spur the growth of SMEs in Tanzania? - Josephat P. Kweka; Fadhili Sooi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
A recent strand of literature on small and medium enterprise (SME) development identifies linkages with large firms as some of the enablers of development and competitiveness. However, there is a dearth of empirical studies on the topic. In this study, we assess the extent and determinants of linkages between SMEs and large firms in Tanzania and to what degree the linkage is an important driver of SME performance. We find that, while linkages with large firms are potentially beneficial for the increased performance of SMEs, the level of such linkages is low in Tanzania and is likely to be influenced by the firm's production capacity, training, exporting, foreign ownership, industry association, and technology partnerships. This implies that the government's efforts to promote SMEs should include policies or programmes that nurture partnerships with large firms.
Keywords: L25; L2; 330; SMEs; firm linkages; SME growth